The expanding functional roles and signaling mechanisms of adhesion G protein–coupled receptors. Issue 1 (6th June 2019) - Morgan, Rory K.; Anderson, Garret R.; Araç, Demet; Aust, Gabriela; Balenga, Nariman; Boucard, Antony; Bridges, James P.; Engel, Felix B.; Formstone, Caroline J.; Glitsch, Maike D.; Gray, Ryan S.; Hall, Randy A.; et al.
Abstract: The adhesion class of G protein–coupled receptors (GPCRs) is the second largest family of GPCRs (33 members in humans). Adhesion GPCRs (aGPCRs) are defined by a large extracellular N‐terminal region that is linked to a C‐terminal seven transmembrane (7TM) domain via a GPCR‐autoproteolysis inducing (GAIN) domain containing a GPCR proteolytic site (GPS). Most aGPCRs undergo autoproteolysis at the GPS motif, but the cleaved fragments stay closely associated, with the N‐terminal fragment (NTF) bound to the 7TM of the C‐terminal fragment (CTF). The NTFs of most aGPCRs contain domains known to be involved in cell–cell adhesion, while the CTFs are involved in classical G protein signaling, as well as other intracellular signaling. In this workshop report, we review the most recent findings on the biology, signaling mechanisms, and physiological functions of aGPCRs. Abstract : Adhesion G protein–coupled receptors (aGPCRs) are the second largest family of GPCRs. They are defined by a large extracellular N‐terminal region containing domains involved in cell–cell adhesion that is linked to a C‐terminal seven transmembrane domain involved in classical G protein signaling and other intracellular signaling. In this meeting report, the authors review the most recent findings on the biology, signaling mechanisms, and physiological functions of aGPCRs.